Carbohydrate intake before and during high intensity exercise with reduced muscle glycogen availability affects the speed of muscle reoxygenation and performance - Ramonas, A.; Laursen, P. B.; Williden, M.; Chang, W.-L.; Kilding, A. E. (European Journal of Applied Physiology, 2023)
Muscle glycogen state and carbohydrate (CHO) supplementation before and during exercise may impact responses to high-intensity interval training (HIIT). This study determined cardiorespiratory, substrate metabolism, muscle oxygenation, and performance when completing HIIT with or without CHO supplementation in a muscle glycogen depleted state. On two occasions, in a cross-over design, eight male cyclists performed a glycogen depletion protocol prior to HIIT during which either a 6% CHO drink (60 g.hr-1) or placebo (%CHO, PLA) was consumed. HIIT consisted of 5 × 2 min at 80% peak power output (PPO), 3 × 10-min bouts of steady-state (SS) cycling (50, 55, 60% PPO), and a time-to-exhaustion (TTE) test. There was no difference in SS VO2, HR, substrate oxidation and gross efficiency (GE %) between CHO and PLA conditions. A faster rate of muscle reoxygenation (%. s-1) existed in PLA after the 1st (? - 0.23 ± 0.22, d = 0.58, P < 0.05) and 3rd HIIT intervals (? - 0.34 ± 0.25, d = 1.02, P < 0.05). TTE was greater in CHO (7.1 ± 5.4 min) than PLA (2.5 ± 2.3 min, d = 0.98, P < 0.05). CHO consumption before and during exercise under reduced muscle glycogen conditions did not suppress fat oxidation, suggesting a strong regulatory role of muscle glycogen on substrate metabolism. However, CHO ingestion provided a performance benefit under intense exercise conditions commenced with reduced muscle glycogen. More research is needed to understand the significance of altered muscle oxygenation patterns during exercise.